Acid pretreatment effect on oxygen migration during lignite pyrolysis. (15th February 2020) - Li, Xiao-hong; Li, Hai-jie; Wang, Ruo-qing; Feng, Jie; Li, Wen-ying
Graphical abstract: Highlights: Coal pretreated by HCl/HF makes COOH be easier into gas during pyrolysis. Ph-OH in coal migrates more into tar after acid pretreatment coal pyrolysis. O increments in n -hexane soluble fraction of tar is mainly from polyphenols. Abstract: To investigate the effect of acid pretreatment on the migration rule of oxygen element during isothermal pyrolysis, Hulunbuir lignite was sequentially pretreated with HCl and HF acid before being pyrolyzed at 650 °C. The products obtained from the pyrolysis of acid-treated coal sample were studied using gas chromatography and elemental analysis. Owing to the influence of the HCl-HF pretreatment, the oxygen migration to char and gas decreased by 3.75% and 2.84%, respectively, while the oxygen migration to coal tar and the n -hexane-soluble fraction increased by 5.07% and 0.4%, respectively. The oxygen-containing functional groups of all the investigated coal and chars are quantitatively estimated through chemical titration and Fourier transform infrared spectroscopy. Results furthermore inferred that the stepwise acid treatment on one hand excludes the oxygen migration from the carboxylic compounds of lignite to gaseous oxygen by eliminating the mineral elements that served as virtual cross-linking points; on the other hand, some of the oxygen-containing functional groups (OH, CO and ROR′) that originally appear in char during lignite pyrolysis can transfer to volatiles because of the acid pretreatment destroying the pore structure of raw coal.